Analisis Pengaruh Persepsi Kebermanfaatan, Keamanan, Kepercayaan dan Kemudahan Terhadap Minat Menggunakan Online Banking Generasi X, Y, dan Z - Husnayetti Husnayetti; Ellya Sestri (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2019)
The purpose of this study is to analyze the influence of perceptions of usefulness, security, trust and ease of interest in using online banking for X, Y and Z generations in the South Tangerang area. Researchers used primary data by distributing questionnaires to respondents (generations X, Y and Z). All samples taken match meet the following criteria: 1) Respondents residing in South Tangerang and 2) have used online banking. The analysis used is multiple linear regression with SPSS software. The results showed that partially for X generation, perceptions of usefulness, security, and ease had a positive effect on interest in using online banking, while the perception of trust had a negative influence on the interest in using online banking in the South Tangerang area. Meanwhile, for Y generation, perceptions of usefulness and convenience have a positive effect on the interest in using online banking while the perception of security and trust negatively affects the interest in using online banking. For the Z generation, perceptions of usefulness, trust and ease in using online banking have a positive effect, while security perceptions negatively affect the interest in using online banking. As for simultaneous analysis there is a significant influence on perceptions of usefulness, security, trust and ease of using online banking with a R2 value of 62.5% for generation X, 61.7% for generation Y and 65.1% for generation Z.